Dental mesowear and microwear for the dietary reconstruction of Quaternary Southeast Asian serows and gorals - Isarankura Na Ayudhya, Jakritip; Merceron, Gildas; Wannaprasert, Thanakul; Jaeger, Jean-Jacques; Chaimanee, Yaowalak; Shoocongdej, Rasmi; Suraprasit, Kantapon (Frontiers in Ecology and Evolution, 2022)
Serows and gorals (Bovidae, Caprinae) are emblematic antelopes distributed in Southeast Asia. They all are nearly threathen or vulnerable species nowadays despite having a more widespread distibution during the Pleistocene. Fossils of three native caprine species, i.e. a Sumatran serow C. sumatraensis, Chinese goral N. griseus, and Himalayan goral N. goral, were recovered from four Pleistocene palaeontological and archaeological sites in Thailand, namely Pha Bong, Khok Sung, Tham Wiman Nakin, and Tham Lod Rockshelter. To investigate dietary changes of these Southeast Asian serows and gorals through the Quaternary, differences in feeding habits and habitat preferences between the Pleistocene and extant populations were examined using the hypsodonty index together with the mesowear II method and the dental microwear texture analysis (DMTA). The hypsodonty index and mesowear-II results showed that Pleistocene and extant caprines were mixed feeders. For the Pleistocene caprine populations, the DMTA results suggested more browsing signals for C. sumatraensis than both Naemorhedus species that were mixed feeders similar to their extant populations. The DMTA demonstrated a considerable dietary overlap among the Pleistocene sympatric caprine populations. The dental microwear results also revealed that the extant C. sumatraensis is a leaf-dominant browser, while the extant N. griseus possibly feeds on seeds or tough food items. These data combined with previous stable carbon isotope analyses reinforce the idea that the restricted ranges of habitats for these extant serow and goral populations have possibly been driven by the Holocene climatic and environmental changes as well as the negative effects of human activities.